Assessment of premenstrual syndrome among reproductive aged Myanmar women - Oo, Htet Htet; Sein, Mya Thanda; Mar, Ohn; Aung, Aye (Asian Journal of Medical Sciences, 2016)
Background: Almost all women experience at least mild degree of one or more premenstrual symptoms during the days before menstruation. Women with premenstrual syndrome (PMS) experience a pattern of severe premenstrual symptoms month after month and premenstrual dysphoric disorder (PMDD) is the extreme, predominantly psychological end of the PMS spectrum. These symptoms hinder some aspect of their family as well as social lives and also interfere their activities at work. Aims and Objectives: This study aimed to assess the prevalence of PMS among reproductive aged Myanmar women from medical field and to investigate the frequency and severity of symptoms experience by the women with PMS. Materials and Methods: All participants were asked to complete a questionnaire derived from Calendar of Premenstrual Experiences (COPE) for two consecutive menstrual cycle to diagnose PMS and PMDD. A cross-sectional descriptive study was conducted in 400 reproductive aged women (between 15 - 45 years) among the medical students, doctors and nurses. Results: Out of 400 subjects, 149 women (37.3%) met DSM-IV criteria for PMS and 251 women (62.7%) did not have PMS. Among PMS women, 81 women (54.4%) had PMDD. The most frequent PMS symptoms were poor concentration (88.6%), irritability (87.3%), ache and pain (81.9%), increased appetite (79.2%) and breast swelling (75.8%). The most frequent symptom in mild and moderate PMS is physical symptom (ache and pain) and that in PMDD was psychological symptom (poor concentration). Conclusion: The prevalence of PMS with high PMDD proportion was found in reproductive aged Myanmar women from medical field. Asian Journal of Medical Sciences Vol.7(4) 2016 39-43